A Review on Frequency Synchronization in Collaborative Beamforming: A Practical Approach - Suleiman , Umar Dauda; Esa, Mazlina; Nik Abd Malik, Nik Noordini; Mohd Yusof, Kamaludin; Mohd Yusoff, Mohd Fairus; Hamid, Mohamad Rijal (Journal of Advanced Research in Applied Mechanics, 2020)
Coherent signal reception from distributed beamforming nodes of virtual antenna array formation requires frequency synchronization of the participating nodes. Signals at the target receiver are out of phase due to unsynchronized local oscillator’s (LO) reference signal of all the nodes in the systems. Practical cases of this problem are considered. In this article, a brief overview is presented of the need for the frequency synchronization and the resulting effect of mitigation avoidance. A variant of the closed-loop feedback algorithm is used to provide LO drifts information to the beamforming transmitters. These feedbacks are used to estimate, correct, and predict the nonlinear LO offsets that will result in near (0) phase offset of the received signal. The algorithms are implemented in software defined radio (SDR) and transmitted through the RF front end of devices like the NI 2920/N210 USRP.